Strategi Kepemimpinan Kantor Kementerian Agama Kabupaten Bekasi - Atikah, Aat; Muhyiddin, Asep; Risdayah, Enok (Tadbir: Jurnal Manajemen Dakwah, 2023)
This abstract aims to determine the profile of the office of the ministry of religion in Bekasi Regency, formulating strategies, implementing strategies, evaluating leadership strategies. The method used in this research is a descriptive method with a qualitative approach. The results of the study show that the office of the ministry of religion in Bekasi Regency implements an operational strategy in its leadership, which is indicated by the indicator that the ministry operates existing resources through special indicators, where the division's ability to recruit human resources through special capabilities determined based on SOPs. In addition, through the operational strategy, it was found that the measurement of employee performance was carried out by the office of the ministry of religion in Bekasi Regency as seen from the results of the reports that were monitored every day, so that the strategy was expected to greatly affect the leadership process to realize the ministry's vision and mission.